2017
DOI: 10.1186/s12890-016-0348-4
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of inhaled corticosteroid particle size on asthma efficacy and safety outcomes: a systematic literature review and meta-analysis

Abstract: BackgroundInhaled corticosteroids (ICS) are the primary treatment for persistent asthma. Currently available ICS have differing particle size due to both formulation and propellant, and it has been postulated that this may impact patient outcomes. This structured literature review and meta-analysis compared the effect of small and standard particle size ICS on lung function, symptoms, rescue use (when available) and safety in patients with asthma as assessed in head-to-head randomized controlled trials (RCTs).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
4
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 44 publications
0
16
4
3
Order By: Relevance
“…Baou EL reported that in a meta-analysis of studies on patients with asthma, no significant differences were observed between smaller size and larger standard size particle of ICS for change in spirometry. Although there was a relationship between smaller particle size and increased delivery to the distal lung, increased deposition in the distal lung did not improve the clinical outcomes in patients with asthma [32]. On the other hand, this study indicated that there may be a certain relationship between the site of airway impairment and the particle size of ICS.…”
Section: Discussioncontrasting
confidence: 61%
“…Baou EL reported that in a meta-analysis of studies on patients with asthma, no significant differences were observed between smaller size and larger standard size particle of ICS for change in spirometry. Although there was a relationship between smaller particle size and increased delivery to the distal lung, increased deposition in the distal lung did not improve the clinical outcomes in patients with asthma [32]. On the other hand, this study indicated that there may be a certain relationship between the site of airway impairment and the particle size of ICS.…”
Section: Discussioncontrasting
confidence: 61%
“…Baou EL reported that in a meta-analysis of studies on patients with asthma, no signi cant differences were observed between smaller size and larger standard size particle of ICS for change in spirometry. Although there was a relationship between smaller particle size and increased delivery to the distal lung, increased deposition in the distal lung did not improve the clinical outcomes in patients with asthma [32]. On the other hand, this study indicated that there may be a certain relationship between the site of airway impairment and the particle size of ICS.…”
Section: Discussioncontrasting
confidence: 61%
“…6 Altering the pattern of particle size distribution, even within this small range, can influence the deposition characteristics of an aerosol. 26…”
Section: Technical Factors To Consider When Selecting An Inhaler Devicementioning
confidence: 99%